Metodologias projetuais nos territórios informais: Heliópolis - Getlinger, Daniela Cristina Vianna (2013)
Nowadays, the biggest population growth occurs in megacities of the developing countries, where extreme forms of modernization coexist with large scale informal urban conditions. In the informal territories of these megacities, large concentration of poverty, social problems along with social and economic dynamics, creative initiatives and sense of urbanity is observed. Considering that currently 1/3 of the world population lives in poor conditions (in slums and distance outskirts), and that the urban poor is the fastest growing population group in the world, it is based on the understanding of the informal territory as part of the city, that new strategies of intervention in the megacity shall be investigated. Issues posed by the social and spatial reality in the megacities of the 21st century, such as quantity, density and new conditions of urbanity, require new instruments of investigation, new vocabulary and concepts and more dynamic design strategies. To intervene in these dynamic territories, more flexible strategies, capable of considering multiple futures, are required. Diverse urbanisms and different programs, rather than stable configutarions of permanent forms. In this sense, the research points to the process of co-creation as an urban design strategy in the informal territories. Methodologies of intervention within the informal territory of Heliópolis are the research object of in this study.